2012
DOI: 10.1063/1.3692966
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fluctuations in globally coupled phase oscillators with general coupling: Finite size effects

Abstract: We investigate the diffusion coefficient of the time integral of the Kuramoto order parameter in globally coupled nonidentical phase oscillators. This coefficient represents the deviation of the time integral of the order parameter from its mean value on the sample average. In other words, this coefficient characterizes long-term fluctuations of the order parameter. For a system of N coupled oscillators, we introduce a statistical quantity D, which denotes the product of N and the diffusion coefficient. We stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…In our discussion in Ref. [12], we suggested that the standard scaling law can be observed in a wide range of systems. We also found that, in the coherent regime of system (1), the asymptotic form of D for large N is represented as…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In our discussion in Ref. [12], we suggested that the standard scaling law can be observed in a wide range of systems. We also found that, in the coherent regime of system (1), the asymptotic form of D for large N is represented as…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, many studies have also focused on the universal scaling law with respect to finite system size N . In fact, it is known that the variance of the order parameter generally decays with N in the order of 1/N independently of the details of the system elements [9][10][11][12]. Such a scaling law is regarded as standard because it applies to a wide range of models.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations